Age of first deciduous tooth eruption in a Portuguese children population: a cross-sectional study - Bárbara Cunha; Manuel Salgado; Francisco Caramelo; Ana Luísa Costa (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2022)
Objectives: To define the timing of the first deciduous tooth eruption in a sample of Portuguese children. Methods: Observational study including a convenience sample of 2115 healthy Portuguese children aged between 1-24 months. A single clinician performed the oral observation under an artificial light source, identifying the first erupted deciduous tooth and registering age (in months). Data were analyzed with IBM® SPSS® v24, R v3.3.2, and Python v3.7.1 (α=0.05). The percentiles of the age of first tooth eruption were determined, along with the cumulative probability curve for both genders and the proportion of first erupted tooth type per gender with its confidence interval. Results: The age of first tooth eruption was slightly inferior in males (mean=7.01 (± 2.24); median=6.0 months; 95% CI [5.8, 6.2]) than in females (mean=7.55 (± 2.41); median=6.5 months; 95% CI [6.3, 6.7]), with a statistically significant difference. The first deciduous tooth erupting was the mandibular central incisor, on average, at 6.94 (± 2.10) months in males and 7.49 (± 2.17) months in females. Conclusions: The present study indicates that, unequivocally, the mandibular central incisor was most often the first deciduous tooth to erupt, and, on average, that happened at 6.94 months for males and at 7.49 months for females.